2002
DOI: 10.4269/ajtmh.2002.67.32
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host and larval habitat distribution on the abundance of African malaria vectors in western Kenya.

Abstract: Abstract. The abundance of anopheline mosquitoes varies substantially among houses within the same villages. Anopheles gambiae sensu stricto is highly anthropophilic, and Anopheles arabiensis is zoophilic; thus, it is often hypothesized that the abundance of An. gambiae and An. arabiensis in a house is associated with the distribution of livestock and humans. In this paper we examined the influence of livestock and human host availability on the distribution and abundance of malaria vectors in the basin region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 22 publications
10
156
2
Order By: Relevance
“…gambiae based on the distance of larval habitats to the closest house (Minakawa et al 1999, Minakawa et al 2002. Most of the Anopheles adults in that study were collected within houses that were less than 300 meters of the closest larval habitat.…”
Section: Resultsmentioning
confidence: 99%
“…gambiae based on the distance of larval habitats to the closest house (Minakawa et al 1999, Minakawa et al 2002. Most of the Anopheles adults in that study were collected within houses that were less than 300 meters of the closest larval habitat.…”
Section: Resultsmentioning
confidence: 99%
“…arabiensis, and An. funestus which are more dominant species during the dry periods [11,30]. The distance between oviposition site and blood host may affect the oviposition choice [17].…”
Section: Spatial and Temporal Distributionmentioning
confidence: 99%
“…The distance between oviposition site and blood host may affect the oviposition choice [17]. [30] showed that immatures of An. gambiae would be found in breeding sites closer to houses and further away from cowsheds and a study [31] showed that significantly more larvae of An.…”
Section: Spatial and Temporal Distributionmentioning
confidence: 99%
“…Closer proximity of a village to a reservoir is associated with higher number 10.1002/2017GH000108 of annual malaria cases because mosquitoes' lifetime flight distance limits malaria transmission far away from their breeding sites (Bomblies, 2014;Cano et al, 2006;Endo & Eltahir, 2016;Gu et al, 2006;Minakawa et al, 2002;Trape et al, 1992;van der Hoek et al, 2003;Zhou et al, 2007). For example, around the Koka Reservoir (N8 ∘ 25 ′ ; E39 ∘ 05 ′ ) in Ethiopia, the annual malaria case rates among people living within 1 km of the reservoir was 2.9 times greater than those living between 1 and 2 km from it, and 19.9 times greater than those living 5 to 9 km from it (Kibret et al, 2009).…”
Section: Introductionmentioning
confidence: 99%